1991
DOI: 10.3133/ofr91310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the synthesis of pyrite and marcasite (FeS<sub>2</sub>) from 0° to 200° C and summary of results

Abstract: Pyrite and marcasite (FeSi) precipitation was studied experimentally from 0 to 200° C under conditions that may have existed during the formation of carbonate-hosted Pb-Zn (Mississippi Valley Type) deposits. Dissolved ferrous iron (from FeSO4 or FeCla), elemental sulfur (S°), and hydrogen sulfide (H^S) were the reactants, with sulfuric acid (H2SO4) or hydrochloric acid (HCI) added to adjust the initial pH to 3.2 or less. A separate series of experiments using added CaCOs was run to examine the acid-neutralizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Calculated pH values for calcite-saturated fluids flowing through limestone rather than through dolostone host rocks are in the same general range as those of dolomite-saturated fluids. Such low pH values are consistent with the presence of abundant hydrothermal marcasite which requires pH values of less than 4.5 to 5.0 to form (Murowchick and Barnes, 1986; Goldhaber and Stanton, 1987;Stanton and Goldhaber, 1991). Low pH values are also consistent with observed aluminosilicate alteration mineralogies (Sverjensky, 1984).…”
Section: Calculated Fluid Chemistriessupporting
confidence: 68%
“…Calculated pH values for calcite-saturated fluids flowing through limestone rather than through dolostone host rocks are in the same general range as those of dolomite-saturated fluids. Such low pH values are consistent with the presence of abundant hydrothermal marcasite which requires pH values of less than 4.5 to 5.0 to form (Murowchick and Barnes, 1986; Goldhaber and Stanton, 1987;Stanton and Goldhaber, 1991). Low pH values are also consistent with observed aluminosilicate alteration mineralogies (Sverjensky, 1984).…”
Section: Calculated Fluid Chemistriessupporting
confidence: 68%
“…See Table 2 for complete microprobe analyses. sible for the enriched arsenian pyrite observed in Alabama coals may be the source (Stanton and Goldhaber, 1991;Goldhaber et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Experimental studies (see Richard et al, 1995) have shown that the formation of marcasite and pyrite is controlled by sulfur speciation and pH. Marcasite is the dominant Fe-disulfide phase formed at the low pH (b 5) when neutral polysulfides (H 2 S 2 ) are present Shoonen and Barnes, 1991;Stanton and Goldhaber, 1991). Polysulfides are, however, metastable , espe- cially in acidic environments (Giggenbach, 1974) typical of coal deposits undergoing early-to middiagenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps the best examples of detrital sulfides in North American MVT deposits are the Polaris mine and Pine Point district, where there are abundant iron sulfides. The presence of abundant marcasite is indicative of low pH (< 4-5; Stanton and Goldhaber, 1991;Goldhaber and Stanton, 1987;Murowchick and Barnes, 1986), consistent with ore-stage carbonate dissolution. Deposition of iron sulfides is a highly effective acid generation process that could produce localized host-rock dissolution.…”
Section: Hydrothermal Mvt Brecciationmentioning
confidence: 95%